2012 International Conference on Emerging Trends in Electrical Engineering and Energy Management (ICETEEEM) 2012
DOI: 10.1109/iceteeem.2012.6494454
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and reliable lung nodule detection using a neural network based computer aided diagnosis system

Abstract: The manual examination of histological images like computed tomography (CT) images by physicians is prone to subjectivity and limited intra and inter-surgeon reproducibility, due to its heavy reliance on human interpretation. As result of which, diagnosis of cancer especially in lungs becomes less accurate and unreliable. So, a computer-aided diagnosis (CAD) system, based on artificial intelligence that efficiently detects nodules of any shape and size, is used for diagnosis without human intervention. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…Other techniques that can be considered for the preprocessing stage are: enhancement filter [70,71], contrast limited adaptive histogram equalization [72],auto-enhancement [73], wiener filter [73], fast Fourier transform [74], wavelet transform [74], anti-geometric diffusion [74], erosion filter [75], smoothing filters [76] and noise correction [76]. Figure 1 gives an illustration of preprocessing applied to a lung CT image, in which an improved distribution of level colors and, consequently, a better visualization of the lung and its structures, is accomplished.…”
Section: Preprocessingmentioning
confidence: 99%
See 1 more Smart Citation
“…Other techniques that can be considered for the preprocessing stage are: enhancement filter [70,71], contrast limited adaptive histogram equalization [72],auto-enhancement [73], wiener filter [73], fast Fourier transform [74], wavelet transform [74], anti-geometric diffusion [74], erosion filter [75], smoothing filters [76] and noise correction [76]. Figure 1 gives an illustration of preprocessing applied to a lung CT image, in which an improved distribution of level colors and, consequently, a better visualization of the lung and its structures, is accomplished.…”
Section: Preprocessingmentioning
confidence: 99%
“…Computational classifier Santos et al [4], Wang et al [25], Choi and Choi [24], Riccardi et al [30], Liu et al [31], Ozekes and Osman [37], Yang, Periaswamy and Wu [39] and Orozco et al [94] Support vector machines (SVM) El-Baz et al [22] Bayesian supervised Cascio et al [26], Ashwin et al [72], Lin et al [95] and Bellotti et al [96] Artificial neural networks (ANN)…”
Section: Authorsmentioning
confidence: 99%
“…The drawback of histogram equalization is that the image brightness is changed after apply this technique. To overcome the limitation of histogram equalization we used Contrast Limited Adaptive Histogram Equalization (CLAHE) technique to enhance CT scan images [9]. The CLAHE algorithm partitions the images into contextual regions and applies the histogram equalization to each one.…”
Section: Preprocessingmentioning
confidence: 99%
“…Ashwin et al (2012) suggested a CAD system for the lung nodule detection using neural network. The contrast limited adaptive histogram method was used to remove the noise presented in medical image and improve the contrast, However the brightness value could be further increase [22]. used Brightness Preserving Bi Histogram Equalization and Adaptive Histogram Equalization methods for contrast enhancement which divide image histogram in two parts mean and median and then process is performed [24].…”
Section: Introductionmentioning
confidence: 99%
“…Surya et al (2015) [11]. Ashwin et al (2012) suggested a CAD system for the lung nodule detection using neural network. The contrast limited adaptive histogram method was used to remove the noise presented in medical image and improve the contrast, However the brightness value could be further increase [22].…”
Section: Introductionmentioning
confidence: 99%